Riquier–Neumann Problem for the Polyharmonic Equation in a Ball - Valery Karachik (Mathematics, 2023)
The Green’s function of the Riquier–Neumann problem for the polyharmonic equation in the unit ball is constructed. Using the obtained Green’s function, an integral representation of the solution to the Riquier–Neumann problem in the unit ball is found.